PENGARUH KEMISKINAN DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI WILAYAH PERKOTAAN ACEH - Muhammad Muhammad; Muhammad Riski; Puti Andiny; Safuridar Safuridar (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
ABSTRAK This study aims to analyze the influence of unemployment and poverty on economic growth in urban areas of Aceh, including Banda Aceh, Lhokseumawe, Langsa, Subulussalam, and Sabang during the 2020–2024 period. The research utilizes secondary data obtained from the Central Bureau of Statistics (BPS). The analytical method employed is panel data regression using the Fixed Effect Model, which was selected based on the results of the Chow Test and Hausman Test. The findings indicate that unemployment has a negative and significant effect on economic growth, implying that an increase in unemployment levels will reduce the economic growth rate in urban Aceh. Meanwhile, poverty has a positive but insignificant effect on economic growth, suggesting that there is no strong statistical evidence that poverty has a real impact on economic growth. Simultaneously, unemployment and poverty exert a significant influence on economic growth, with an Adjusted R-squared value of 0.469961, indicating that 46.99% of the variation in economic growth can be explained by both variables. These findings emphasize the importance of policies focused on job creation, improvement of labor quality, and more effective poverty alleviation programs to support inclusive and sustainable economic growth in urban areas of Aceh. Keywords: unemployment, poverty, economic growth, panel data, urban Aceh